PRODUKSI KARYA SENI RUPA MOOI INDIE DALAM BENTUK EDIBLE ART SEBAGAI STRATEGI INOVASI PEMASARAN WARISAN REMPAH DI SAECA CAFÉ, SURAKARTA - Waryanti, Dessy Rachma; Primadewi, Nerfita; Anggoro, Albertus Rusputranto Ponco (Abdi Seni, 2025)
This study explores the design of edible art inspired by the aesthetic tradition of Mooi Indie painting and the sensory qualities of Indonesian spices through a collaborative community engagement project with the MSME partner, Saeca. Integrating visual art and molecular gastronomy, the project aims to produce intermedia artworks that are both culturally resonant and experientially rich. Employing the Design Thinking framework—Empathize, Define, Ideate, Prototype, and Test—the research applies a qualitative approach to analyze the symbolic, material, and sensory characteristics of traditional Indonesian spices within the context of art history. The resulting edible artworks reinterpret the idyllic and romanticized themes of Mooi Indie while showcasing the complexity and cultural significance of indigenous spices. These creations offer a novel intersection between food and fine art, functioning as sensory-based cultural expressions that respond to contemporary aesthetic and market needs. The findings highlight the potential of edible art as a medium for cultural storytelling, interdisciplinary innovation, and the preservation of local heritage through multisensory experience design.